2017
DOI: 10.1016/j.canep.2017.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Time trends for prostate cancer mortality in Brazil and its geographic regions: An age–period–cohort analysis

Abstract: The increase in prostate cancer mortality rates in Brazil and its regions was mainly due to population aging. The differences in mortality rates and APC effects between regions are related to demographic differences and access of health services across the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 32 publications
3
20
0
1
Order By: Relevance
“…This is the first study that investigates the incidence of PCa using age-period-cohort models in South Korea. Most of previous studies using age-period-cohort model are limited to mortality issue [2,12]. Our results showed that PCa incidence rate had an increasing trend from 2003 to 2011.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…This is the first study that investigates the incidence of PCa using age-period-cohort models in South Korea. Most of previous studies using age-period-cohort model are limited to mortality issue [2,12]. Our results showed that PCa incidence rate had an increasing trend from 2003 to 2011.…”
Section: Discussionsupporting
confidence: 46%
“…2020;52(1):301-308 screening for PCa. However, whether PSA screening could compensate the mortality rate of PCa ultimately remains controversial [2]. After USPSTF recommendations in 2008 that encouraged those over 75 years not to perform routine PSA screening, PCa incidence rate started to decrease in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SIM, with SIH/SINASC, has been used in linkage studies (Kropiwiec et al, 2017; Paixao et al, 2018), characterization of trends and regional patterns in (cause-specific) maternal and infant mortality (Victora and Barros, 2001), trends and disparities in cancer mortality (Alves et al, 2009; Girianelli et al, 2014; Braga et al, 2017; Prado da Fonseca et al, 2018), among others. SIM has good coverage and quality, and death characterization.…”
Section: Databases Used In Health Outcomes/policy Research In Brazilmentioning
confidence: 99%
“…Certain susceptibility factors, including heavy alcohol intake, tobacco use, high calorific diet and chemical dyes, have been identified as potential susceptibility factors for cancer ( 3 ). An aging population, increased environmental pollution and longer life expectancy, have also contributed to increased incidence rates of cancer ( 4 ). However, the underlying pathogenic mechanisms of cancer remain to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%